The Effect of Resistance Training with Boldenone Consumption, Ziziphus jujuba Extract and Gallic Acid on Annexin-5 and Caspase-3 Genes Expression in Cardiac Tissue of Male Wistar Rats - Asieh Abbasi Daloii (Islamic Azad University, 2016)
Introduction: Herbal medicines have gained growing popularity and have been used worldwide as alternative and complementary medicine and food supplements. The aim of this study was to investigate the effect of resistance training with boldenone consumption, ziziphus jujuba extract and Gallic acid on annexin-5 and caspase-3 genes expression in cardiac tissue of male Wistar rats. Methods: In this experimental study, 42 male Wistar rats aged 8-12 weeks with mean weight of 195±7.94g were randomly divided into seven groups: control, boldenone, jujube extract + boldenone, Gallic acid + boldenone, resistance training + boldenone, resistance training + jujube extract + boldenone, resistance training + Gallic acid + boldenone. Resistance training program included six weeks of climbing a ladder for 5 sessions, 3 sets, 5 repetitions and one-minute resting between sets with 50% 1RM in the first week and 100% 1RM in the final week. The drug was injected in the hamstring in depth once a week on an appointed day. After anesthesia, the autopsy was performed and cardiac tissue was dissected. Data were analyzed using paired sample t-test, One-way ANOVA and Scheffe post hoc at the P